Washing treatment impact on print quality of screen printed knitted fabrics - Stančić,Mladen (2016)
ABSTRACT The surface of textile materials is highly textured, commonly in non-uniform ways. Because of this texture effect, textile surface appears rougher and more porous than other printing substrates, which can cause excessive ink penetration during printing process. Next, washing process is very important factor because it influences ink characteristics on printed samples as well as structural changes of the textile substrate. The aim of this paper is to determine the influences of washing process and different mesh tread count used for printing on print quality. This will be obtained by using spectrophotometric analysis, and GLCM image processing method for print mottle estimation. The results of this research show that increasing number of washing processes leads to higher color differences reproduction color in comparison to printed materials before washing. It also shows that textile surface texture has a great influence on print mottle as well as that number of washing treatment series can generate variations of solid-tone print uniformity.